2016
DOI: 10.1139/gen-2015-0205
|View full text |Cite
|
Sign up to set email alerts
|

Multi-locus DNA barcoding identifies matK as a suitable marker for species identification in Hibiscus L.

Abstract: The genus Hibiscus L. includes several taxa of medicinal value and species used for the extraction of natural dyes. These applications require the use of authentic plant materials. DNA barcoding is a molecular method for species identification, which helps in reliable authentication by using one or more DNA barcode marker. In this study, we have collected 44 accessions, representing 16 species of Hibiscus, distributed in the southern peninsular India, to evaluate the discriminatory power of the two core barcod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“…The BLAST analysis based on the matK locus showed incorrect identification of H. sabdariffa and ambiguous identification of both H. rosa-sinensis and M. arboreus (Table 03). These findings are contradictory to those reported by Poovitha et al (2016) who found that matK was a suitable barcode for Hibiscus including H. rosa-sinensis and H. sabdariffa. Hence, the purity of the species or the evolution of the species at different localities may influence the effectiveness of DNA barcoding to identify species.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…The BLAST analysis based on the matK locus showed incorrect identification of H. sabdariffa and ambiguous identification of both H. rosa-sinensis and M. arboreus (Table 03). These findings are contradictory to those reported by Poovitha et al (2016) who found that matK was a suitable barcode for Hibiscus including H. rosa-sinensis and H. sabdariffa. Hence, the purity of the species or the evolution of the species at different localities may influence the effectiveness of DNA barcoding to identify species.…”
contrasting
confidence: 99%
“…The success of species identification using DNA barcoding depends very much on the taxa in question, as much as the utilised marker (Amandita et al, 2019). For example, in Hibiscus, including H. rosa-sinensis and H. sabdariffa, matK was found to be the most suitable when compared to rbcLa, trnH-psbA and ITS2 (Poovitha et al, 2016). However, to discriminate Hibiscus syriacus from its adulterants correctly, ITS2 was recommended (Liu et al, 2014).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…For DNA barcoding, total genomic DNA was isolated as per the method described by Saghai‐Maroof, Soliman, Jorgensen, and Allard (1984). DNA barcoding was carried out using ITS2, trnH‐psbA, rbc L, and mat K markers as described before (Poovitha, Nithaniyal, Balaji, & Parani, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The herbarium voucher specimen (SRMH000142) was deposited in the SRM IST Herbarium at the SRM Institute of Science and Technology, Kattankulathur, India (Herbarium curator: Dr. E. Pandian, Email: pandiane@ srmist.edu.in). Total genomic DNA from O. gratissimum was extracted using the CTAB method (Doyle and Doyle 1987), with some modifications (Poovitha et al 2016). A whole-genome DNA sequencing library was constructed using the Nextera XT Library Prep Kit.…”
mentioning
confidence: 99%